2017
DOI: 10.1007/s11356-017-0543-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of chromium status in the revegetated flora of a tannery waste site and microcosm studies using earthworm E. fetida

Abstract: Chromium from tannery waste dump site causes significant environmental pollution affecting surrounding flora and fauna. The primary aims of this study were to survey vegetation, investigate the degree of soil pollution occurring near tannery waste dump site and make a systematic evaluation of soil contamination based on the chromium levels found in plants and earthworms from the impacted areas. This paper presents the pollution load of toxic heavy metals, and especially chromium, in 10 soil samples and 12 spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Alkaloids, being one of the largest group of phytochemicals in plants have pronounced effect on humans which have led to development of pain killer medication [ 26 ]. Moreover, these alkaloids have also been act as insect repellents as mentioned by [ 27 ]. According to [ 28 ], A. indica crude extracts showed the presence of alkaloids, glycosides, flavonoids, saponins, tanins, and phenolic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Alkaloids, being one of the largest group of phytochemicals in plants have pronounced effect on humans which have led to development of pain killer medication [ 26 ]. Moreover, these alkaloids have also been act as insect repellents as mentioned by [ 27 ]. According to [ 28 ], A. indica crude extracts showed the presence of alkaloids, glycosides, flavonoids, saponins, tanins, and phenolic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The high Cr concentrations in the lavender shoots (843.9 mg/kg  47.0 mg/kg) grown in highly Cr-contaminated soils were close to the threshold concentration of Cr hyperaccumulators (1,000 mg/kg) (Baker and Brooks 1989). The results demonstrate that the lavender plant could be considered as a potential hyperaccumulator in Cr-contaminated sites, with the high toxicity of Cr to plants resulting in a rare ideal option for Cr phytoremediation (Nirola et al 2018). However, the low plant yield and low growth rate of lavender in such highly Cr-contaminated soil may restrict its phytoremediation efficiency.…”
Section: Phytomanagement Efficiency Of Lavendermentioning
confidence: 99%
“…It has been reported that a level of Cr > 5.2 mg/kg in soil can induce toxicity in plants such as Helianthus annuus (Davies Jr. et al 2002). However, the stress effects on plant growth depend on a variety of soil conditions, such as pH, organic matter, and oxidation-reduction potential (Nirola et al 2018). In general, the Cr(VI) forms of chromate and dichromate are highly soluble in water, while Cr(III) is less soluble due to higher mobility of Cr(VI) in the soil environment.…”
Section: Growth Of Lavender Plantmentioning
confidence: 99%
“…Furthermore, it generates free radicals and reactive oxygen species (ROS). Because of its high solubility in water, Cr VI is very active in the environment, making this metal, derived from steel manufacturing and leather tanning, a dangerous pollutant [2,3]. The pollution of soils and water bodies with Cr is a serious problem in ecosystems, since methods for its transformation into a less toxic form remain unknown [4].…”
Section: Introductionmentioning
confidence: 99%